ANALYSIS OF STUDENTS' LEARNING INTEREST ON PHYSICS LESSON AT SENIOR HIGH SCHOOL 6 MUARO JAMBI - Astuti, Yuli (EduFisika: Jurnal Pendidikan Fisika, 2021)
This study aims to measure the interest of students of SMA Negeri 6 Muaro Jambi towards physics subjects. The subjects in this study were 59 students majoring in science class XI MIPA at SMA Negeri 6 Muaro Jambi. The object of this research is interest in learning physics. The method used was a case study research method with a qualitative approach. Data collection was done by using an interest questionnaire. Data were analyzed descriptively. The results of this study indicate that students of class XI MIPA at SMA Negeri 6 Muaro Jambi have a good interest in studying physics. The average interest of class XI MIPA students is 89.9%.